The Full Value of Vaccine Assessments Concept—Current Opportunities and Recommendations - Richard G. White; Nicolas A. Menzies; Allison Portnoy; Rebecca A. Clark; Cristiana M. Toscano; Charlotte Weller; Marta Tufet Bayona; Sheetal Prakash Silal; Ruth A. Karron; Jung-Seok Lee; Jean-Louis Excler; Jeremy A. Lauer; et al. (Vaccines, 2024)
For vaccine development and adoption decisions, the ‘Full Value of Vaccine Assessment’ (FVVA) framework has been proposed by the WHO to expand the range of evidence available to support the prioritization of candidate vaccines for investment and eventual uptake by low- and middle-income countries. Recent applications of the FVVA framework have already shown benefits. Building on the success of these applications, we see important new opportunities to maximize the future utility of FVVAs to country and global stakeholders and provide a proof-of-concept for analyses in other areas of disease control and prevention. These opportunities include the following: (1) FVVA producers should aim to create evidence that explicitly meets the needs of multiple key FVVA consumers, (2) the WHO and other key stakeholders should develop standardized methodologies for FVVAs, as well as guidance for how different stakeholders can explicitly reflect their values within the FVVA framework, and (3) the WHO should convene experts to further develop and prioritize the research agenda for outcomes and benefits relevant to the FVVA and elucidate methodological approaches and opportunities for standardization not only for less well-established benefits, but also for any relevant research gaps. We encourage FVVA stakeholders to engage with these opportunities.